Sleep Disturbances in Autoimmune Neurologic Diseases: Manifestation and Pathophysiology - Yin, Dou; Chen, Sheng; Liu, Jun (Frontiers in Neuroscience, 2021)
Autoimmune neurologic diseases are a new category of immune-mediated disease demonstrating a widely varied spectrum of clinical manifestations. Recently, sleep disturbances in patients with autoimmune neurologic diseases have been reported to have an immense negative impact on the quality of life. Excessive daytime sleep, rapid eye movement sleep behavior disorder (RBD), and narcolepsy are the most frequent sleep disorders associated with autoimmune neurologic diseases. Sleep disturbances might be the initial symptoms of disease or persist throughout the course of the disease. In this review, we have discussed sleep disturbances in different autoimmune neurologic diseases and their potential pathophysiological mechanisms.